Analisis durasi belajar terhadap hasil belajar matematika - Fitri, Lailatul (Maliki Interdisciplinary Journal, 2024)
Learning duration and mathematics learning outcomes are two important aspects in the learning process. Study duration refers to the time a person invests in studying, which can have a significant effect on learning success. Meanwhile, mathematics learning outcomes are influenced by various internal and external factors of students, such as learning motivation, learning methods, and environmental support. This research aims to analyze the relationship between learning duration and mathematics learning outcomes, as well as efforts that can be made to improve mathematics learning outcomes by considering the learning duration factor. Various strategies such as scheduling effective study time, using efficient study techniques, learning independence, and involving parents and teachers in supporting students’ learning duration can help improve understanding and learning achievement in mathematics. By understanding and managing study duration optimally, it is hoped that students can achieve better and more sustainable mathematics learning outcomes.